Relationship of genetic polymorphisms with smoking behavior in the Malay population in Kelantan - A Rozak, Nur Iwani (2015)
Smoking addiction is a leading cause of diseases and mortality worldwide. However despite the well-known associated risk to health, smoking prevalence is still increasing worldwide. Nicotine is the main addictive substance in cigarettes that is responsible for the development as well as maintenance of smoking addiction. Genetic variables appear to play a key role in every aspect of nicotine addiction. Therefore genes involved in pharmacodynamic and pharmacokinetic of nicotine are logical candidates for nicotine addiction. Among listed candidate genes published for their known association with nicotine, four of them were selected which were nicotinic acetylcholine receptor (nAChR) rs2273502 and rs2236196, serotonin transporter 5HTTLPR and serotonin receptor 5HT2A and their relationships with smoking behavior in the Malays were investigated in this thesis. The study involved 248 Malay male smokers and 248 Malay male nonsmokers. DNA was extracted from leucocytes. The PCR product of nAChR rs2273502 and rs2236196 and 5HT2A were digested with restriction enzymes AfeI, Sau96I and HpaII respectively. The 5HTTLPR genotypes were analyzed by using PCR method and the results were classified as short (S) alleles or long (L) alleles. No mutation of rs2273502 (TT genotype) was detected in the nonsmoker group whilst the frequencies of homozygous CC genotype and heterozygous CT in nonsmokers were 75.8% and 24.2%, respectively. While in smokers, the frequencies were 73.4%, 2.0% and 24.6%, respectively. No significant difference was observed in genotype (χ2=5.106, p=0.078) and allele (χ2=1.064, p=0.302) frequencies among both group. The frequency distribution for rs2236196 polymorphism in smoker group was 80.6% for homozygous AA genotype while in nonsmoker 77.0%. No mutation (GG genotype) was detected in both groups. The AG genotype for smoker group was 19.4% while in nonsmoker group 23.0%. There was no significant difference observed in the genotype (χ2=0.979, p=0.323) and allele frequencies (χ2=0.863, p=0.353) between both groups. The genotype frequencies for 5HT2A polymorphism in smokers are CC= 10.1%, TT= 46.8% and CT=43.1%. While for nonsmokers are CC=8.1%, TT=46.4% and CT=45.6%. There was no significant difference observed in the genotype 5HT2A (χ2=0.724, p=0.696) and allele frequencies (χ2=0.075, p=0.784). On the other hand, for 5HTTLPR polymorphism, the frequencies of variant alleles S, L and heterozygous SL in nonsmokers were 39.1%, 11.3% and 49.6%, respectively. While in smokers, the frequencies of variant alleles S, L and heterozygous SL were 41.1%, 12.9% and 46.0%, respectively. No significant difference in the frequency distribution of alleles was found between smokers and nonsmokers of genotype 5HTTLPR (χ2 = 0.734, p=0.693) and allele frequencies (χ2 = 0.004, p=0.947) for both group studied. In conclusion, the nicotinic acetylcholine receptor (nAChR) rs2273502 and rs2236196, serotonin transporter (5HTTLPR) and serotonin receptor (5HT2A) polymorphisms were not found to be associated with the smoking behavior in Malay male subjects in Kelantan.